MORPHOLOGICAL CHANGES IN THE REPRODUCTIVE ORGANS OF WOMEN WITH EXPERIMENTAL METABOLIC SYNDROME - Gulhayo I. Saidmurodova ,; Ravshan J. Usmonov ,; Abror Sh. Shamuratov , (Central Asian Journal of Medicine, 2024)
In recent years, scientists have been paying increasing attention to metabolic syndrome in women of reproductive age, as it has become one of the most common causes of reproductive diseases. Population studies show that the prevalence of metabolic syndrome in women is 15-20%, while in the structure of reproductive system pathologies, metabolic syndrome accounts for 30-35% and is more frequently detected in patients with recurrent hyperplastic processes. The frequency of endometriosis reaches up to 70%. Numerous studies have demonstrated an increased risk of developing endometrial, cervical, ovarian, and breast cancer in women with metabolic syndrome. It has been established that the prevalence of metabolic syndrome (MS) in women with polycystic ovary syndrome (PCOS) is 43-47%, while the frequency of PCOS in women with MS is 24%. Notably, almost every woman (91%) with PCOS has some components of MS, including dyslipidemia (60%), hypertriglyceridemia (35%), obesity (67%), and arterial hypertension (45%). Most morphological and physiological studies have focused on morphological changes in the heart and pancreas. However, there are few studies dedicated to morphological changes in the reproductive organs of women with metabolic syndrome. Taking this into account, we investigated morphological changes in the uterus and ovaries as the subject of our research. The obtained results revealed that the main morphological substrate consists of changes in the form of destruction and defragmentation in the uterus and ovaries.